2016
DOI: 10.1159/000447281
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of IBD: Batf as a Key Driver of Disease Activity

Abstract: Background: Inflammatory bowel diseases (IBDs) represent a group of chronic immune-mediated disorders that are influenced by a genetic predisposition and additional environmental triggers. Genome-wide association studies strongly implicate that a number of immune system-related genetic variations are critically contributing to the initiation and promotion of intestinal inflammation. Especially the identification of the strong association of a series of single nucleotide polymorphisms including interleukin (IL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…IBD usually occurs in young adults and is closely associated with inheritance, infection and immune function (3). IBD is harmful to health with characteristics including a high recurrence rate, high canceration rate and poor prognosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…IBD usually occurs in young adults and is closely associated with inheritance, infection and immune function (3). IBD is harmful to health with characteristics including a high recurrence rate, high canceration rate and poor prognosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Batf positive T cells are thought to actively contribute to the T cell mediated component of colitis. Further, unlike STAT3, the absence of Batf did not influence the intestinal homeostasis ex vivo [34].…”
Section: The Influence Of Th17 Cells On Ibdmentioning
confidence: 83%
“…Recently, it was reported that not only neutrophils but also CD4 + T helper (Th) cells have important roles in the pathogenesis of IBD. These studies have focused on Th17 cells because the IL23/Th17/IL17A pathway is an important therapeutic target in IBD patients . However, the role of IL17A in colitis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have focused on Th17 cells because the IL23/Th17/IL17A pathway is an important therapeutic target in IBD patients. [33][34][35] However, the role of IL17A in colitis remains controversial. The levels of IL17A produced by Th17 cells are increased in both the colonic mucosa and serum of IBD patients.…”
Section: Discussionmentioning
confidence: 99%